2009
DOI: 10.1158/1535-7163.mct-08-1118
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Noxa/Mcl-1 axis determine sensitivity of small cell lung cancer to the BH3 mimetic ABT-737

Abstract: To understand the molecular basis for variable sensitivity to the BH3 mimetic drug ABT-737, the abundance of Bcl-2 family members was assayed in a panel of small cell lung cancer cell lines whose sensitivity varied over a 2-log range. Elevated Noxa and Bcl-2 levels directly correlated with sensitivity to ABT-737, whereas Mcl-1 levels were similar in all cell lines tested regardless of sensitivity. Transgenically enforced expression of Noxa but not Bcl-2 resulted in increased sensitivity to ABT-737 in multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
55
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 39 publications
6
55
0
Order By: Relevance
“…In many cell types, Noxa has also been shown to mediate proteasome degradation of Mcl-1 (9,10). However, in SCLC, we have shown that Noxa-mediated degradation of Mcl-1 was lost in all four cell lines examined, either because Mcl-1 levels were insensitive to changes in Noxa expression or because endogenous Noxa expression was absent (5). This observation suggests that maintenance of Mcl-1 expression in the face of stimuli that induce Noxa may be involved in the pathogenesis or progression of SCLC.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…In many cell types, Noxa has also been shown to mediate proteasome degradation of Mcl-1 (9,10). However, in SCLC, we have shown that Noxa-mediated degradation of Mcl-1 was lost in all four cell lines examined, either because Mcl-1 levels were insensitive to changes in Noxa expression or because endogenous Noxa expression was absent (5). This observation suggests that maintenance of Mcl-1 expression in the face of stimuli that induce Noxa may be involved in the pathogenesis or progression of SCLC.…”
mentioning
confidence: 72%
“…One important factor in the development of chemotherapy resistance is the overexpression of prosurvival members of the Bcl-2 family (2). In SCLC, overexpression of Bcl-2 has been shown (3), and Bcl-X L and Mcl-1 are also expressed at varying levels as well (4,5). BH3-mimetic drugs represent an exciting new development in cancer therapeutics designed to counteract the effects of prosurvival Bcl-2 family proteins by blocking their ability to bind and inactivate the BH3 domain-containing proapoptotic Bcl-2 family members, thus allowing the proapoptotic proteins to directly or indirectly induce permeablization of the outer mitochondrial membrane and activation of the intrinsic apoptotic caspase cascade (6).…”
mentioning
confidence: 99%
“…Importantly, abolishing sunitinib-mediated induction of MCL-1 by the combination with a subtoxic dose of sorafenib was associated with a dramatic sensitization to treatment with lower dose of sunitinib, while neither of these treatments evoked apparent cell death ( Figure 3C and Supplemental Figure 5, A and B). The sunintinib/ABT737 combination did not show such synergism, but if anything, sunitinib seemed to desensitize cells to ABT737 treatment, possibly through MCL-1 stabilization, which is known to mediate resistance to ABT737 (40,41). Replating equal numbers of surviving HCT116 cells from all the previous conditions in fresh medium without drugs showed that the antiproliferative effect of the sunitinib/sorafenib combination was irreversible, as cells pretreated with this combination could not recover and died within the ensuing 48 hours, while cells from other treatments proliferated normally ( Figure 3D).…”
Section: Sunitinib Exerts Dual Effects On Mcl-1 and Mtor In Tolerant Andmentioning
confidence: 95%
“…High-affinity binding of BH3 peptides to both BCL-2 and BCL-X L is mediated primarily by interactions in two hydrophobic pockets, termed P2 and P4, and navitoclax specifically binds to these P2 and P4 pockets 39 . The efficacy of ABT-263 and its related compound, ABT-737, has been demonstrated in lung cancer 8,[41][42][43][44][45][46] . Because of the key role of MCL1 in protecting malignant cells against anticancer treatments, combinatorial therapy with BH3-binding molecules such as navitoclax may enhance the therapeutic effects of radiotherapy and other treatments.…”
Section: The Role Of Mcl1 and Its Targeted Therapy In Lung Cancermentioning
confidence: 99%